Penggunaan Media Sosial Dalam Perspektif Bimbingan Konseling Islam - Firdania, Mala; Subhi, Muhammad Rifa’i (AL-MIKRAJ Jurnal Studi Islam dan Humaniora, 2024)
The use of social media has become an integral part of everyday life, including in the context of Islamic guidance and counseling. This paper aims to investigate the role of social media as a strategic tool in assisting the Islamic counseling guidance process. Various social media platforms, such as Facebook, Twitter, Instagram, and WhatsApp, offer various opportunities to communicate, share knowledge, and provide support to individuals who need Islamic counseling guidance. In this context, this article explores the positive impact of using social media in supporting Islamic guidance and counseling practices, while considering the challenges and risks. The analysis was carried out through literature perspectives and case studies to present a comprehensive picture of how social media can be optimized as a strategic tool in Islamic counseling guidance.